Collagen synthesis in normal and osteoarthritic human cartilage. - Lippiello, L (1977)
Collagen metabolism in osteoarthritic human articular cartilage was compared to that in normal cartilage and was also correlated with the degree of severity of the osteoarthritic lesion as determined by a histological-histochemical grading system. No correlation was apparent between the concentrations of DNA, hydroxyproline, and hydroxylysine and the degree of severity of the osteoarthritic lesion (except in far-advanced lesions). Similarly, there was no correlation in levels of these components in tissues from the normal vs. osteoarthritic group. The similarity of the values of the ratio hydroxylysine/hydroxyproline in osteoarthritic tissue compared with normal, and the lack of variation in these with increasing severity of the disease process argues against the possibility that osteoarthritis is associated with a major shift in the synthesis of type II collagen to type I. [3H]Proline incorporation into osteoarthritic cartilage was increased fourfold as compared to normal cartilage and varied with advancing histological-histochemical grade. Measurement of the specific activity of insolubilized hydroxyproline-containing material of the cartilage matrix, as an index of the turnover of collagen, showed a sixfold increase in osteoarthritic cartilage which also varied with grade. These data suggest that collagen synthesis in these tissues is substantially greater than in nonosteoarthritic tissues and varies directly with the severity of the disease process up to a point and then varies inversely as the lesion becomes more severe.